RELATIONSHIP BETWEEN CONSUMER BEHAVIOR, DISCOUNTS AND PURCHASE DECISION - Untung Surapati; Syariful Mahsyar (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The use of promotional discount on food is a phenomenon which is interesting among the business as one of the strategies of marketing. The use of the discount in the restaurant fast -food can be a stimulus to the decision of purchasing consumer. In this study using a sample of as many fast food restaurant visitors. With respondents as many as 100 respondents. Research is trying to see how large the stimulus the against making decisions purchase of the consumer in the restaurant fast -food Samarinda. Results of the study showed that variabel consumers behavior towards the discount effect significantly, whereas the relationship variable discount to the decision of buying influence positive but not significant and variable behavior of consumers against the decision of buying influence positive but not significant.